TEACHING VOCABULARY TO JUNIOR HIGH SCHOOL STUDENTS THROUGH SNAKE -WORD GAME - Delmayanti Delmayanti; Muhammad Al-Hafizh (Journal of English Language Teaching, 2013)
Snake Word Game is a chain word game that teacher writes a letter, after that the firs student must write a word with that letter. The following student writes a word beginning with the last letter of previous word. Snake Word Game expected to help teacher in teaching English vocabulary and make students easier to memorize some vocabularies. ABSTRAK Snake word Game adalah sebuah permainan kata berantai yang mana guru menulis huruf,   kemudian siswa pertama harus menulis kata yang awalnya harus sama dengan kata yang di tulis guru. Siswa selanjutnya menulis kata yang awal katanya dimulai dari huruf akhir kata sebelumnya. Snake word game diharapkan  membantu guru dalam mengajar kosa kata bahasa Inggris dan membuat siswa mengingat kosa kata dengan lebih mudah. Permainan ini membutuhkan kerja sama kelompok.